Nitrogen fluxes from the landscape are controlled by net anthropogenic nitrogen inputs and by climate - Howarth, Robert; Dennis Swaney; Gilles Billen; Josette Garnier; Bongghi Hong; Christoph Humborg; Penny Johnes; Carl-Magnus MÃ¶rth; Roxanne Marino (Frontiers in ecology and the environment, 2012)
The flux of nitrogen (N) to coastal marine ecosystems is strongly correlated with the ânet anthropogenic nitrogen inputsâ (NANI) to the landscape across 154 watersheds, ranging in size from 16 kmÂ² to 279 000 kmÂ², in the US and Europe. When NANI values are greater than 1070 kg N kmâ»Â² yrâ»Â¹, an average of 25% of the NANI is exported from those watersheds in rivers. Our analysis suggests a possible threshold at lower NANI levels, with a smaller fraction exported when NANI values are below 1070 kg N kmâ»Â² yrâ»Â¹. Synthetic fertilizer is the largest component of NANI in many watersheds, but other inputs also contribute substantially to the N fluxes; in some regions, atmospheric deposition of N is the major component. The flux of N to coastal areas is controlled in part by climate, and a higher percentage of NANI is exported in rivers, from watersheds that have higher freshwater discharge.